Influence of sowing time on efficiency of chemical and biological management of anthracnose of cowpea - D.K. BANYAL, RITU MAWAR* and (Indian Phytopathology, 2017)
Cowpea is grown in various agro-climatic zones of India for seed and fodder purposes. Anthracnose caused by Colletotrichum dematium (Pers.) Grove is the most devastating and causes substantial yield losses in this crop. Anthracnose severity was maximum in the early sown, while minimum in late sown crop irrespective of all the treatments. In the interaction analyses, all the biological and chemical treatments were significantly superior at Palampur location irrespective of date of sowing. On the basis of pooled average at Jhansi, the disease incidence ranged from 10.5-22.9% compared to Palampur where it ranged from 3.7-22.7%. The influence of sowing date on incidence of anthracnose was significant at both the locations. Early sowing leads to higher disease incidence than late sowing.